(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Problem Based Learning (PBL) is the major curriculum delivery system in our academy. Due to COVID-19, the face-to-face sessions were converted into synchronous online version. Thus, the objective of this study was to compare perception on face-to-face and synchronous online PBL of MBBS first- and second-year students in basic sciences and PBL tutors. Method: This is a descriptive, cross-sectional study. A validated questionnaire was sent to the participants using google form. Quantitative data were entered as numbers and percentage and for qualitative data, thematic analysis was done. Result: Students from first (N=48) and second year (N=55) and their tutors (N=10) were involved in this study. Majority of the participants were satisfied with synchronous online PBL, while half of them agreed this could be alternative to face-to-face PBL. The benefits were exposure to newer technology enabling easier participation, flexibility, and useful in adverse situation. However, students agreed or strongly agreed that the group dynamic 71(68.9%), critical thinking 62(51.2%) and team spirit 72(69.9%) were unsatisfactory. Tutors six (60%) also had difficulty in assessing students in different aspects of PBL. Participants suggested that solving technical issues, timely feedback from tutors and self-motivation among students could help in smooth conduction of PBL. Conclusion: This study showed that synchronous online PBL can be better alternative when it is not possible to conduct face-to-face PBL. Despite its limitation, particularly in achieving soft skills of PBL like teamwork and critical thinking, participants have suggested that technical support, timely training and self-motivation can overcome these.